One-step purification of histone-like protein (HU) from Halobacillus litoralis - Ghadam, Parinaz; Mollasalehi, Maryam (Acta Biologica Szegediensis, 2015)
The histone-like protein (HU) in bacteria is a small, basic, heat-stable protein that is involved in cell division and compression of the bacterial genome into a nucleoid. HU exists as a homodimer in most gram-positive bacteria such as Bacillus subtilis and as a heterodimer in enterobacteria such as Escherichia coli. The structure of HU, similar to other proteins, may change during purification, which may reduce the value of the investigation. Therefore, in this study, HU was purified in one step using an affinity chromatography column CNBr-activated Sepharose 4B matrix without using high-speed centrifugation and salting out methods. It was observed that the molecular weight and immunochemical properties of HU from Halobacillus litoralis were the same as those of HBsu (HU from B. subtilis).